KONSTRUKSI HUKUM PEMBIAYAAN MURABAHAH DAN WAKALAH DALAM SATU TRANSAKSI PADA BANK BTPN SYARIAH; TELAAH FATWA DSN-MUI NOMOR 04/DSN-MUI/IV/2000 - Wahyudi, Anjar K, (Fakultas Syariah INSURI Ponorogo, 2019)
The purpose of this study is to find out how the construction of the DSN-MUI fatwa on murabaha financing and time in one transaction at PT Bank BTPN Syariah. This research is a qualitative research with a normative juridical approach that uses the Statue Approach method and the Case Approach method. The technique of analyzing legal materials in this study uses descriptive analysis techniques. Murabaha contract accompanied by wakalah contract at PT Bank BTPN Syariah based on DSN-MUI fatwa construction number: 04 / DSN-MUI / IV / 2000 dated April 1, 2000 concerning Murabahah in the first stipulation in paragraph 9 stated: